Stop that frog! - Winkler, Henry, 1945-; Oliver, Lin (Winkler, Henry, 1945- Here's Hank, 2014)
When the principal has to be away from school at a conference, Hank's class agrees to take care of the principal's special pet frog, and Hank is chosen to take the frog home for the weekend.